Construction of a dephosphorylation-mediated chemiluminescent biosensor for multiplexed detection of DNA glycosylases in cancer cells. Issue 17 (1st April 2022) - Liu, Ming-Hao; Wang, Chuan-Rui; Liu, Wen-Jing; Tian, Xiao-rui; Xu, Qinfeng; Zhang, Chun-Yang
Abstract : We develop a dephosphorylation-mediated chemiluminescent biosensor for multiplexed detection of DNA glycosylases in cancer cells. Abstract : DNA glycosylases are engaged in the base excision repair process and play a vital role in maintaining genomic integrity. It remains a challenge for multiplexed detection of DNA glycosylases in cancer cells. Herein, we demonstrate the construction of a dephosphorylation-mediated chemiluminescent biosensor for multiplexed detection of human alkyladenine DNA glycosylase (hAAG) and uracil DNA glycosylase (UDG) in cancer cells. In this biosensor, the generation of chemiluminescence signals relies on the dephosphorylation of 3-(2′-spiroadamantyl)-4-methoxy-4-(3′′-phosphoryloxyphenyl)-1, 2-dioxetane (AMPPD) catalyzed by alkaline phosphatase (ALP). We design a bifunctional double-stranded DNA (dsDNA) substrate, a biotin-labelled poly-(T) probe, and two capture probes for the hAAG and UDG assay. This assay involves four steps including (1) the cleavage of the bifunctional dsDNA substrate induced by DNA glycosylases, (2) the recognition of the 3′-OH terminus of the primer by TdT and the subsequent TdT-mediated polymerization reaction, (3) the construction of the AuNPs–dsDNA–ALP nanostructures, and (4) the streptavidin-alkaline phosphatase (SA-ALP)-initiated dephosphorylation of AMPPD for the generation of an enhanced chemiluminescence signal. By taking advantage of the unique features of TdT-mediated polymerization and the intrinsic superiority of the ALP-AMPPD-based chemiluminescence system, this biosensor exhibits good specificity and high sensitivity with a detection limit of 1.53 × 10 −6 U mL −1 for hAAG and 1.77 × 10 −6 U mL −1 for UDG, and it can even quantify multiple DNA glycosylases at the single-cell level. Moreover, this biosensor can be applied for the measurement of kinetic parameters and the screening of DNA glycosylase inhibitors, holding great potential in DNA damage-related biomedical research and disease diagnostics.